2002
DOI: 10.1074/jbc.m201369200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Inhibits Human Trophoblast Invasion through AT1 Receptor Activation

Abstract: Trophoblast implantation depends, in part, on the controlled production of plasmin from plasminogen, a process regulated by plasminogen activators and plasminogen activator inhibitors. We have determined that angiotensin II (Ang II) stimulates plasminogen activator inhibitor-1 (PAI-1) synthesis and secretion in human trophoblasts in a time-and concentration-dependent manner. Our results indicate that Ang II activates PAI-1 gene expression through the AT1 receptor and involves the calcium-dependent activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 52 publications
4
78
2
6
Order By: Relevance
“…In vitro studies using a transformed cytotrophoblast cell line (HTR-8/SVneo) demonstrated a potent inhibition of invasive potential, which is abrogated by selective inhibition of type 1 (AGTR1, AT1) receptor signalling (Xia et al 2002). The physiological significance of this result was supported by a recent report demonstrating Ang II stimulates proliferation, but inhibits differentiation, of cytotrophoblast cells from first trimester villous tip outgrowths in culture (Araki-Taguchi et al 2008).…”
Section: Introductionsupporting
confidence: 72%
“…In vitro studies using a transformed cytotrophoblast cell line (HTR-8/SVneo) demonstrated a potent inhibition of invasive potential, which is abrogated by selective inhibition of type 1 (AGTR1, AT1) receptor signalling (Xia et al 2002). The physiological significance of this result was supported by a recent report demonstrating Ang II stimulates proliferation, but inhibits differentiation, of cytotrophoblast cells from first trimester villous tip outgrowths in culture (Araki-Taguchi et al 2008).…”
Section: Introductionsupporting
confidence: 72%
“…CHO-AT1 cells were cultured as described previously (33) and plated at 1.5 ϫ 10 6 in 10-cm wells in RPMI 1640 medium supplemented with 5% fetal bovine serum. The suspended cells were transiently transfected with various expression plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were plated in six-well dishes (21 cm 2 per well) at a density of 5 ϫ 10 5 cells per well for RNA isolation, total cellular protein isolation, and transient transfection experiments (34). For some experiments cells were plated on coverslips for fluorescent microscopy.…”
Section: Rat Neonatal Cardiac Myocyte Culture and Glutamine Treatment-mentioning
confidence: 99%
“…The cell lysate was centrifuged at 14,000 rpm for 30 min, and the protein concentration in the supernatant was determined using BCA (Pierce) reagent (34).…”
Section: Rat Neonatal Cardiac Myocyte Culture and Glutamine Treatment-mentioning
confidence: 99%